Marketing communication strategy of Finnish and Japanese mobile game developers and publishers - Cheng, Yi-Tung (2017)
Both the marketing communication strategy of mobile game industry and the industry itself have been drastically evolving in the past years since the development of computation, data transfer and communication technology on mobile devices. Marketing communication has been considered a significant part in marketing strategy, but the marketing communication strategy, activity and channels were not well investigated so far. In this study, 9 SMEs Finnish and Japanese mobile game developers and publishers provided their experience on how they built up marketing communication strategy for their targeting markets, which marketing communication channels they have used and how they chose the channels. Through this study, it is understood that the marketing communication strategy and activities of both Finnish and Japanese mobile game developers and publishers were highly constrained by their financial resource and their own experience on the activities and channels. On the other hand, some difference in user preference in media channels potentially caused the phenomena that some media channels are only used by Japanese mobile game developers and publishers but not by Finnish ones. This study revealed that utilizing marketing communication channels in marketing activity effectively and financially efficiently on the targeted market based on the understanding of user preference of the targeted market could be the potential keys to succeed in the targeted market.